The Effect Of Reward On Employee Performance At PT BRI Asuransi Indonesia (BRI Insurance) Makassar Branch - Widayani Ridwan, Fahra; Guntur, H. Muhammad; Lutfhi Siraj, Muhammad (Pinisi Business Administration Review, 2024)
This research aims to determine the effect of giving rewards on employee performance at PT BRI Asuransi Indonesia (BRI Insurance) Makassar branch partially and simultaneously. This type of research is a type of quantitative research using variable simple paradigm designs. The population in this study were all employees who worked at the PT office. BRI Asuransi Indonesia (BRI Insurance) Makassar Branch. The sample in this study was 35 employees of PT. BRI Asuransi Indonesia (BRI Insurance) Makassar Branch selected randomly. Data collection techniques are carried out through observation, filling out questionnaires and documentation. The data obtained from the research results were analyzed using the SPSS version 24 software program which consists of validity and reliability tests on research instruments, descriptive statistical analysis and inferential statistical analysis. Based on the research results, it shows that: (1) The percentage of rewards obtained is: 72.62% is in the Good category and the achievement percentage of employee performance is 78.45% in the Good category. (2) The correlation coefficient obtained is 0.337, which means that the relationship between Rewards and Employee Performance is low. The coefficient of determination obtained is 0.114 or 11.4%, which means that the influence of rewards on employee performance is 11.4% (assuming that other factors are constant). So it can be concluded that giving rewards has a significant effect on employee performance at PT BRI Asuransi Indonesia (BRI Insurance) Makassar branch.Keywords: Reward, BRI Insurance, Employee Performance